G214 The Best Way to Teach Developmental Assessment – a Single Blinded Randomised Study Comparing Teaching Models. (4th June 2013) - Feyereislova, S; Nathan, D
Abstract : Aims: Developmental assessment is a core paediatric competency but research demonstrates teaching gaps. This single blinded, randomised controlled study compares three teaching approaches to developmental assessment in a large group setting based on student's self perception and objective competency assessment. Methods: Students were randomised into one of the following (1) a didactic lecture followed by self study with online resources (control group) (2)a didactic presentation and small group tutorial (small group) (3) a combined didactic lecture and interactive component using audio-visual equipment (Interactive Developmental Teaching-IDT group). The audiovisual system is widely and cheaply available nationally and utilised one teacher and 2 children, and aimed at 45 students.Competency scores (based on the RCPCH scoring system, and adapted for undergraduates), mean score of self reported confidence and degree of motivation were compared. Results: 114 students participated. A statistically significant difference between the mean assessment scores was demonstrated for the small group (38, 0; 95% CI 36, 5–39, 6) and IDT group (37, 9; 95% CI 36, 5–39, 4) as compared to the control group (34, 8; 95% CI 33, 2–36, 4). Students' self reported confidence, acquisition of knowledge and degree of motivation to practise after the teaching was higher in the IDT and small group compared to the didactically taught (control) group. The teaching cost, if measured by trainer's time, was one fifth in the IDT group compared to the small group teaching. Conclusions: The IDT is an effective teaching method in large groups, improves competencies compared to didactic lecturing and is as useful as small group teaching. Adoption of the IDT appears to facilitate learning in this important domain and can be feasibly delivered with falling ratios of teachers to students.